2020
DOI: 10.1042/bcj20190730
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanism of sphingosine 1-phosphate clearance from blood

Abstract: The interplay of sphingosine 1-phosphate (S1P) synthetic and degradative enzymes as well as S1P exporters creates concentration gradients that are a fundamental to S1P biology. Extracellular S1P levels, such as in blood and lymph, are high relative to cellular S1P. The blood-tissue S1P gradient maintains endothelial integrity while local S1P gradients influence immune cell positioning. Indeed, the importance of S1P gradients was recognized initially when the mechanism of action of an S1P receptor agonist used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
(56 reference statements)
2
29
0
Order By: Relevance
“…S1E). While adipose tissue homogenates showed similar S1P levels in SK1 fatKO mice and WT mice, S1P is found in micromolar amounts in plasma and even higher amounts in whole blood from erythrocytes (19)(20)(21), and therefore it is likely that these high levels obscured the differences in tissue S1P that would be expected based on reduced mRNA in the HFD-fed SK1 fatKO mice. These data also suggest that SPHK1 in adipocytes does not contribute to circulating levels of S1P, but rather acts in a localized fashion within the tissue.…”
Section: Resultsmentioning
confidence: 92%
“…S1E). While adipose tissue homogenates showed similar S1P levels in SK1 fatKO mice and WT mice, S1P is found in micromolar amounts in plasma and even higher amounts in whole blood from erythrocytes (19)(20)(21), and therefore it is likely that these high levels obscured the differences in tissue S1P that would be expected based on reduced mRNA in the HFD-fed SK1 fatKO mice. These data also suggest that SPHK1 in adipocytes does not contribute to circulating levels of S1P, but rather acts in a localized fashion within the tissue.…”
Section: Resultsmentioning
confidence: 92%
“…Circulating S1P is mainly sourced from the SphK1 in erythrocytes ( 48 ). However, a recent study has found that SphK2 also determines the circulating level of S1P in the liver, where it dictates S1P clearance via a route of dephosphorylation, re-phosphorylation and lysis ( 49 ). Circulating S1P is undoubtedly implicated in whole-body metabolic regulation, but its physiological effects remain elusive.…”
Section: Action Modes Of Sphingosine Kinasementioning
confidence: 99%
“…When detectable, the highest levels of S1P were found in the brain, while the lowest were measured in skin, BAT, and liver (Figure S3C). Recently, Kharel et al (2020) demonstrated in murine models that indeed the liver is the primary site for clearance of S1P from the blood. According to this model, blood S1P is converted, via a cell surface phosphatase, to sphingosine at the hepatocyte surface.…”
Section: Sphs and S1psmentioning
confidence: 99%